2011
DOI: 10.1186/1471-2296-12-64
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a short-course in improving knowledge and skills on evidence-based practice

Abstract: BackgroundTo assess the effectiveness (change in knowledge and skills measured by the Fresno test) of a short course in Evidence Based Practice (EBP) carried out in a group of family medicine residentsMethodsBefore-after study. Participants' were 152 Family Medicine residents in their second year of the training programme. Settings were Primary Care Teaching Units in Catalonia. Intervention was comprised of a four half-day training course designed to develop the knowledge and skills required to practice eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…47). This observed effect size is consistent with intervention studies that have used the Fresno test or a revised version of the original Fresno as the instrument for measuring changes in knowledge and skills [60][61][62][63]. However, these reported effect sizes were interpreted from EBP competence studies in disciplines other than nursing that used alternative approaches to EBP training, over variable periods of time.…”
Section: Ebp Competencesupporting
confidence: 75%
“…47). This observed effect size is consistent with intervention studies that have used the Fresno test or a revised version of the original Fresno as the instrument for measuring changes in knowledge and skills [60][61][62][63]. However, these reported effect sizes were interpreted from EBP competence studies in disciplines other than nursing that used alternative approaches to EBP training, over variable periods of time.…”
Section: Ebp Competencesupporting
confidence: 75%
“…Six studies reported question development results using the Fresno test. Of the six Fresno test articles, three reported a significant increase in the ability to form a clinical question [14][15][16], one reported no significant change [17], and two reported only an overall score [12,18]. Although the overall scores improved significantly, there was no separate reporting on the question specific to formulating a clinical question.…”
Section: Searchable Clinical Questionsmentioning
confidence: 96%
“…For example, to receive full credit, a user might choose an appropriate MeSH term and explain why searching with that MeSH term is better than performing a keyword search. All six studies reporting Fresno test scores showed a significant increase in overall scores post-intervention [12,[14][15][16][17][18]. Four of the studies also separately reported performance on the subsections of the test; all four reported significant skill improvement on the MED-LÉSÍE searching question [^] Article selection.…”
Section: Searchable Clinical Questionsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is found that interactive, close to practice training with adequate continuous support is more cost effective than traditional off site training courses. 10 , 11 Charandabi and associates in a cluster randomized trial found peer education using existing human resources and infrastructure as a useful strategy for imparting education and improving performance in a large group of family planning service providers. 12 At present there is no organized continuous medical education programme, offered by Pakistan medical licensing authority or medical universities for in-service health care providers of public & private sector, due to lack of policy and scarcity of human and financial resources.…”
Section: Discussionmentioning
confidence: 99%